2014
DOI: 10.1021/ie502837d
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active and Stable Ni–SiO2Prepared by a Complex-Decomposition Method for Pressurized Carbon Dioxide Reforming of Methane

Abstract: A series of Ni−SiO 2 catalysts was synthesized by the complex-decomposition method using different amino acids as complexing agents and fuels and nickel nitrate and tetraethoxysilane as precursors of Ni and SiO 2 , respectively. For comparison, ammonium hydroxide and acetic acid were also used as complexing agents and fuels. Characterization by XRD, TEM, and N 2 adsorption−desorption at low temperature indicated that the structural and textural properties of the Ni−SiO 2 catalysts were strongly dependent on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…As shown in Figure 1, all samples exhibited similar diffraction peaks, and in particular, the diffraction peak at 2θ ≈ 23°was attributed to amorphous silica species. 35 Moreover, the diffraction peaks at 2θ = 37°, 43°, 63°, 75°, and 79°can be ascribed to the (111), ( 200), (220), (311), and (222) planes of cubic NiO, 26,27 suggesting that the crystal morphology of the sample did not change when prepared with or without citric acid. However, for the intensity of diffraction peaks, obvious differences showed for Ni/SiO 2 and Ni−C/SiO 2 .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…As shown in Figure 1, all samples exhibited similar diffraction peaks, and in particular, the diffraction peak at 2θ ≈ 23°was attributed to amorphous silica species. 35 Moreover, the diffraction peaks at 2θ = 37°, 43°, 63°, 75°, and 79°can be ascribed to the (111), ( 200), (220), (311), and (222) planes of cubic NiO, 26,27 suggesting that the crystal morphology of the sample did not change when prepared with or without citric acid. However, for the intensity of diffraction peaks, obvious differences showed for Ni/SiO 2 and Ni−C/SiO 2 .…”
Section: Resultsmentioning
confidence: 97%
“…For the supported Ni catalyst, a lower dispersion of Ni is the obstacle for CDR. Liu and co-workers 26,27 observed that Ni dispersion was significantly promoted by complexation of the Ni 2+ with various complexants. Moreover, many organic ligands, such as acetic acid, ethylenediamine, or L-arginine, were added as a complexant in the process of Ni impregnation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8) showed Ni2p 3/2 peak was centered at 854.2 eV and accompanied by an uptake satellite peak at 860 eV for each sample, which was the typical characteristic peak for Ni 0 . Compared with the standard binding energy (BE) of Ni 0 at 852 ± 0.4 eV [63], all of the Ni 2p BEs of spent catalysts were shifted to higher values. This shift indicated that the interactions between Ni species and support species were significantly enhanced during the reforming process [64].…”
Section: Characterization Of the Spent Catalystsmentioning
confidence: 93%
“…For the DRM reaction, nickel based catalysts were more practical in industry because of their cost effectiveness compared to noble metals. However, nickel based catalysts suffered from deactivation due to deposited carbon and Ni sintering in the DRM process. In addition, several side reactions occurred on Ni-based catalysts, such as CH 4 decomposition, CO disproportionation, a reverse water gas shift reaction (RWGS, CO 2 + H 2 → CO + H 2 O, Δ H 298K = 41.19 kJ mol –1 ), and so on, which led to the result that the H 2 /CO ratio of the final products was not equal to 1. Among them, RWGS was usually considered the most responsible for the results that the H 2 /CO obtained was usually less than 1. …”
Section: Introductionmentioning
confidence: 99%